Teknis Pengelolaan Dana Zakat pada Lembaga Amil Zakat - Supandi Rahman (Scimadly Publishing, 2022)
The role of zakat as an instrument of poverty alleviation certainly cannot be denied, mainly if it is managed professionally and institutionalized rather than only being channeled directly to those in need. At this point, the position of the formal institutions managing zakat plays a crucial role. Departing from this, this research is directed to find out more about the activities of zakat fund management in the Gorontalo District BAZNAS. This research uses descriptive qualitative research. The research results show that zakat fund management activities in the Gorontalo District BAZNAS consist of zakat collection and management activities, distribution activities, and secretarial and reporting activities, each of which has dynamics and requires our attention.